Determining Ice-Sheet Uplift Surrounding Subglacial Lakes with a Viscous Plate Model - Walker, Ryan T.; Werder, Mauro A.; Dow, Christine F.; Nowicki, Sophie M. J. (Frontiers in Earth Science, 2017)
We develop a viscous model of plate bending suitable for studying ice-sheet flexure due to subglacial lake filling and draining, and apply this model to determine the area of ice-sheet uplift surrounding a subglacial lake. The choice of a viscous model reflects our interest in Antarctic subglacial lakes, which can fill and drain on time scales of months to decades. Experiments with idealized lake shapes show that the size of the uplift area relative to lake area depends on subglacial water pressure and ice-sheet thickness, with the viscous material parameters scaling the magnitude of uplift rate within this area. The water pressure therefore has a strong control on the evolution of the lake shape and related subglacial hydrological development, but is not yet well constrained by observations. Due to the likelihood that ice flexure will affect subglacial lake filling and draining, we suggest that the insights of this study should be applied to development of a realistic ice sheet-hydrological coupled model.